Sideline care abrasions and lacertions - Bouchard, M. (The Physician and Sportsmedicine, 2005)
Abrasions and lacerations commonly occur during athletic activities. Physicians providing sideline coverage who make adequate preparations, including a well-stocked medical bag, can easily manage these injuries. Abrasions are typically irrigated and then covered with a topical antibiotic and adhesive dressing. Lacerations are treated with local anesthesia, irrigation, and appropriate wound closure using sterile technique. Follow-up for both conditions is necessary to monitor for signs of infection and to ensure a good cosmetic result.